Women entrepreneurs in indigenous communities. The case of Tiquipaya (Bolivia) - Padilla-Meléndez, Antonio; Ciruela-Lorenzo, Antonio Manuel (My University, 2014)
This paper analyzes the factors that affect the activities of indigenous women entrepreneurs of the region of Tiquipaya (Bolivia). Enablers and barriers to entrepreneurship as well as social capital are considered. Based on the analysis of forty-two face-to-face interviews with female and male entrepreneurs, and intermediaries in the area of the valley and mountain range areas of the region of Tiquipaya, the characteristics of these entrepreneurs, the barriers and facilitators, and the role of social capital have been extracted. As main contributions, firstly, it has been proposed a comprehensive conceptual framework for the context. Secondly, it has been found that, contrary to what one might think being indigenous does not affect so much as the fact of being a woman, as a key element for developing successful entrepreneurial activities.
The paper continues as follows. After a literature review on gender and entrepreneurship and indigenous entrepreneurship, an integrated research framework is proposed. Next, the methods and main findings are summarized. The discussion and conclusions close the paper.
Keywords: Mujeres - Trabajo; Pueblos indígenas - Bolivia; Women entrepreneurs; Indigenous communities; Bolivia